Peningkatan Hasil Belajar Matematika Siswa dengan Penerapan Model Pembelajaran Discovery Learning SMP Negeri 2 Barru - Putri, Munadya; Handayani, Sry; Dahlan, Muhammad (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2025)
This study aims to determine how the influence and improvement of learning outcomes with the application of the Discovery Learning model in mathematics learning of class VIII students of SMP Negeri 2 Barru. The research method used was classroom action-based research (PTK) conducted at SMP Negeri 2 Barru, Barru District, Barru Regency, South Sulawesi Province. The participants or subjects of this study were students of class VIII.3 SMP Negeri 2 Barru. This study was attended by 24 students of class VIII.3 SMP Negeri 2 Barru, consisting of 13 boys and 11 girls. The research was conducted from August to October 2024. The results of cycle I research showed that only 41.67% of the 24 students in the class passed. While from the table of research results of cycle II, 4 people or 16.67% have not been able to meet the completeness, while those who achieve the completeness results are 20 people or 83.33%. Comparison of the results of the two cycles shows the average number (mean) of learning evaluation results increased from 62.92% to 80.83% after improving the shortcomings of the Discovery Learning model implemented. Likewise, the completeness of student learning increased from research cycle I to research cycle II.